Students’ Listening Comprehension By Using English Breaking News - Tri Wahyuni Umagapit; Silvani Umar Ali; Hujaefa Hi. Muhamad; Samsudin Hi Adam (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to determine listening comprehension using Breaking News English in third semester English students at Khairun University, Ternate. This research uses quantitative descriptive methods, this research involves 25 participants, research instruments use tests and documentation. The results obtained from the Listening Skills Test were that 16 students out of 25 students in the class were able to answer the questions very well. Research findings regarding listening comprehension showed that, of the 25 students, 16 (64%) were in the "very good" category, 4 (16%) were in the "Good" category, 2 (8%) were in the "fair" category. good category". "category", 3 (12%) are in the "low" category. Third semester English students have an average listening comprehension score of 88.48 which means they are classified as "Very Good". From these results it can be concluded that the listening comprehension of third semester English students at Khairun University using Breaking News English was categorized as very good.